2021
DOI: 10.3390/biomedicines9091093
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Lipid-Soluble Micronutrients with Hepatic Steatosis among Adults in the United States

Abstract: Lipid-soluble micronutrients may be beneficial to non-alcoholic fatty liver disease due to their important roles in metabolism and maintaining tissue functions. Utilizing 2017–2018 National Health and Nutrition Examination Survey, this study examined the potential overall and race/ethnicity-specific (black, Hispanic and white) associations of dietary lipid-soluble micronutrients (α-tocopherol, retinol, vitamin D, β-carotene and total carotenoids) with hepatic steatosis. The analysis included 4376 adults (1037 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 66 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, research suggests that sex is an important factor associated with hepatic physiology and pathology [ 11 ]. Our previous study also found significantly higher rates of hepatic steatosis in men than in women [ 10 ]. Therefore, based on the criteria for the new nomenclature and definition of MASLD, the current study examined the overall and sex-specific associations of serum levels of lipid-soluble micronutrients including α-tocopherol, γ-tocopherol, retinol (vitamin A), 25-hydroxy-vitamin D (25(OH)D), and six major carotenoids (α-carotene β-carotene, α-cryptoxanthin, β-cryptoxanthin, combined lutein and zeaxanthin, and lycopene) with MASLD among adults in the United States, utilizing 2017–2018 Health and Nutrition Examination Survey (NHANES) data.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Furthermore, research suggests that sex is an important factor associated with hepatic physiology and pathology [ 11 ]. Our previous study also found significantly higher rates of hepatic steatosis in men than in women [ 10 ]. Therefore, based on the criteria for the new nomenclature and definition of MASLD, the current study examined the overall and sex-specific associations of serum levels of lipid-soluble micronutrients including α-tocopherol, γ-tocopherol, retinol (vitamin A), 25-hydroxy-vitamin D (25(OH)D), and six major carotenoids (α-carotene β-carotene, α-cryptoxanthin, β-cryptoxanthin, combined lutein and zeaxanthin, and lycopene) with MASLD among adults in the United States, utilizing 2017–2018 Health and Nutrition Examination Survey (NHANES) data.…”
Section: Introductionmentioning
confidence: 67%
“…We previously assessed associations between the dietary intakes of major lipid-soluble micronutrients and hepatic steatosis with the adjustment of most of the cardiometabolic risk factors (history of diabetes, history of hypertension, BMI, etc.) [ 10 ]. Thus, in this study, we further examined the associations of serum levels of lipid-soluble micronutrients with newly defined MASLD, which would provide a more complete picture for understanding the relationships between micronutrients and the disease condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of hydro-alcoholic extract of spinach reduced the expression of proinflammatory cytokine TNF-α and enhanced the expression of PPAR-γ in the livers of NAFLD rats at prevention and treatment phases [ 106 ]. Dietary vitamin E such as α-tocopherol has potential protective effects against steatosis [ 107 ].…”
Section: Treatment Options For Nafld and Nash Based On Modulation Of Gut Microbiota Intrahepatic Immunity And Metabolic Signaling Pathwaymentioning
confidence: 99%